2011
DOI: 10.2528/pier11031104
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Tdie-Tdpo Method for Studying on Transient Responses of Some Wire and Surface Structures Illuminated by an Electromagnetic Pulse

Abstract: Abstract-An efficient hybrid method, based on time-domain integral equation (TDIE) and time-domain physical optics (TDPO), is proposed for studying on transient electromagnetic responses of some wire and surface structures illuminated by an electromagnetic pulse (EMP), respectively. Two groups of triangular-type basis functions are used to expand the currents on both of them. The derived hybrid TDIE-TDPO equations are solved by marching-on-in-time (MOT) scheme. In comparison with the full TDIE-based MOT metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…6. It is demonstrated that the transient currents obtained by the MOD-based TDIE-TDPO method decrease exponentially in the late-time, with no instability which may appear in some MOT-based hybrid schemes [31]. number increases in Fig.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
“…6. It is demonstrated that the transient currents obtained by the MOD-based TDIE-TDPO method decrease exponentially in the late-time, with no instability which may appear in some MOT-based hybrid schemes [31]. number increases in Fig.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
“…Besides methods in frequency domain, analysis of wide-band reflected signals directly in time domain [37][38][39][40][41][42] began to emerge since time-domain physical optics (TDPO) was proposed by Sun [25] in 1994. Most of PO and GO-based high frequency methods in both frequency and time domain have been implemented and used widely, except timedomain version of iterative physical optics which considers multiple scattering directly in time domain.…”
Section: Time-domain High Frequency Theory For Combinative Targetmentioning
confidence: 99%
“…Time-domain integral-equation (TDIE) [1][2][3][4][5][6] methods have enjoyed widespread engineering applications, especially the analysis of broadband electromagnetic scattering. When analyzing the scattering from perfect electric conductor (PEC), the TDIE methods require a discretization of the scatterer surface and do not call for absorbing boundary conditions in the finite difference time domain [7,8].…”
Section: Introductionmentioning
confidence: 99%